Assessment of play behaviours and social interactions of two blind girls - Kobal Grum, Darja (Anthropological notebooks, 2014)
The play behaviours and social interactions of two blind preschool girls with no additional disabilities are described. The data obtained from the assessment protocol indicated that they demonstrated limited play behaviours and compromised social interactions. The results reinforce the variability of social competence skills in young children with visual impairments.
Keywords: predšolski otroci; otroška igra; socialna integracija; otroštvo; slepota; razvoj otroka; vedenje v igri; socialne interakcije; študije; Japonska